Pengaruh Kesiapan Siswa dan Pemanfaatan Teknologi Informasi Komunikasi terhadap Kebijakan Merdeka Belajar Menyongsong Era Industri 5.0 - A. Erni Ratna Dewi; Hasmirati Hasmirati (Madrasah Tsanawiyah DDI Cilellang, 2022)
This study examines the effect of student readiness and the use of ICT on the implementation of independent learning policies in welcoming the industrial era 5.0. This type of research is descriptive quantitative with a survey approach. Data collection techniques were carried out by observation, questionnaires and documentation. The population of this study were all teachers of SMA Negeri 20 Makassar City. Determination of the sample was carried out by purposive sampling using accidental sampling technique, then as many as 40 teacher respondents were recruited who got the task of providing online learning systems to their students. Data analysis was carried out quantitatively with the stages of validity and reliability test analysis, classical assumption test and multiple linear regression analysis. The results of the study found that: 1) simultaneously the variables of student readiness and the use of ICT had a positive and significant effect on the independent learning policy in welcoming the industrial era 5.0; 2) partially each variable, namely student readiness and use of ICT, has a positive and significant influence on the policy of independent learning in welcoming the industrial era 5.0; 3) the dominant student readiness variable has a positive and significant effect on the independent learning policy in welcoming the industrial era 5.0; and 4) the independent learning policy variable shows a negative regression coefficient value, so it is interpreted to have decreased. This means that not all education actors understand the policy of free learning in welcoming the industrial era 5.0.